2022
DOI: 10.1038/s41393-022-00786-x
|View full text |Cite
|
Sign up to set email alerts
|

Guideline for the management of neurogenic bowel dysfunction in spinal cord injury/disease

Abstract: INTRODUCTION: Almost all people with spinal cord injury/disease (SCI/D) suffer from neurogenic bowel dysfunction (NBD), with a considerable impact on quality of life. The Association of the Scientific Medical Societies in Germany (AWMF e.V.) guideline for NBD in SCI/D aims to provide practice-oriented support for the care of patients with NBD resulting from congenital or aquired SCI/D. The guideline describes the diagnosis and bowel management of NBD in people with SCI/D. Thus, treatment processes in acute med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(77 citation statements)
references
References 41 publications
0
39
0
4
Order By: Relevance
“…As many as 60% of individuals in one study reported adverse effects on life activities, altering their lifestyle due to irregular bowel movements associated with problems of recurrent abdominal discomfort, constipation, and/or fecal incontinence requiring treatment [ 4 ]. To facilitate education for all, the PVA Clinical Practice Guidelines for neurogenic bowels have recently been updated by the Consortium for Spinal Cord Medicine [ 11 ] and have affirmed/complemented the recent neurogenic bowel guidelines put forward by the Association of the Scientific Medical Societies in Germany [ 12 ].…”
Section: Neurogenic Bowel After Spinal Cord Injurymentioning
confidence: 99%
See 4 more Smart Citations
“…As many as 60% of individuals in one study reported adverse effects on life activities, altering their lifestyle due to irregular bowel movements associated with problems of recurrent abdominal discomfort, constipation, and/or fecal incontinence requiring treatment [ 4 ]. To facilitate education for all, the PVA Clinical Practice Guidelines for neurogenic bowels have recently been updated by the Consortium for Spinal Cord Medicine [ 11 ] and have affirmed/complemented the recent neurogenic bowel guidelines put forward by the Association of the Scientific Medical Societies in Germany [ 12 ].…”
Section: Neurogenic Bowel After Spinal Cord Injurymentioning
confidence: 99%
“…People with neurogenic bowel will need thorough evaluation beginning with a comprehensive medical history. This should include past medical history, allergies, medications, family history, social environment/resources, and a thorough review of systems, including neurologic diagnoses and functional impairments that might contribute to GI symptoms, bowel, and defecation problems [ 11 , 12 , 37 ]. It is important to determine the duration, severity, and progression of any GI problems, as well as the current bowel care program for emptying [ 11 , 37 ].…”
Section: Comprehensive Evaluation For Neurogenic Bowelmentioning
confidence: 99%
See 3 more Smart Citations